Della Walker (Mrs. Clinton Walker) residence, interior (1950)
Image of furnished living room in the house originally designed by Frank Lloyd Wright. Presents a couch with pillow, carpet and a vase full of flowers. Shows the Pacific Ocean with large rocks from the view of the interior looking out through the front windows.